PR MANAGEMENT IN INCREASING ALUMNI PARTICIPATION IN THE AL-QUR’AN SCIENCE EDUCATION CENTER - Amin, Muhammad Fathul; Manshur, Umar; Agus R, Abu Hasan; Hefniy, Hefniy; Jazilurrahman, Jazilurrahman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Public Relations Management in Increasing Alumni Participation is one way to foster and develop harmonious relations between institutions and alumni in establishing close relationships with alumni. Because the success of an educational institution organization in achieving its mission and objectives is determined by the role of alumni both internally and externally. Based on this, there are three issues that are the main study in this research, namely: first, How is Public Relations Management Planning to Increase Alumni Participation at the Al-Qur’an Science Education Center Nurul Jadid Paiton; second, How is the Implementation of Public Relations Management in Increasing the Participation of Alumni at the Al-Qur’an Science Education Center Nurul Jadid Paiton; third, How to Evaluate Public Relations Management in Increasing Alumni Participation at the Al-Qur’an Science Education Center Nurul Jadid Paiton. This research uses a qualitative approach with a type of field study. Data collection is done by observation, interviews and documentation. While data analysis using triangulation techniques. The results of this study indicate that: First, Public Relations Management Planning in Increasing Alumni Participation at the Nurul Jadid Paiton Al-Qur’an Education Center is carried out based on a public relations work meeting. Namely a. Introducing the importance of madrasas to Alumni b. Get moral and financial assistance c. Provide information to Alumni of program implementation. d. Know the needs of alumni. Second, the implementation of public relations in increasing the participation of alumni at the Nurul Jadid Paiton Al-Qur’an Education Center through several methods/tools, such as distributing brochures, installing banners, promoting institutions through the media etc. Third, a public relations evaluation conducted at the Nurul Jadid Paiton Al-Qur’an Education Center in increasing alumni participation is in two ways, namely, direct and quarterly evaluations (before the odd semester, after the odd semester before the class increase). The evaluation includes: active participation and passive participation.